2021
DOI: 10.1111/mec.16250
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected post‐glacial colonisation route explains the white colour of barn owls (Tyto alba) from the British Isles

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(52 citation statements)
references
References 78 publications
2
50
0
Order By: Relevance
“…Populations isolated by large water bodies have accumulated substantial genetic differences as, for example, the higher F ST in the Canary and Cyprus islands ( fig. 1 c and table 1 ), and reflect the importance of water as a barrier to dispersion in this species ( Machado et al 2021 ). On the mainland, and as described for the American barn owl ( Machado et al 2018 ), major mountain ranges act as significant obstacles to migration for European barn owls and can generate genetic structure.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Populations isolated by large water bodies have accumulated substantial genetic differences as, for example, the higher F ST in the Canary and Cyprus islands ( fig. 1 c and table 1 ), and reflect the importance of water as a barrier to dispersion in this species ( Machado et al 2021 ). On the mainland, and as described for the American barn owl ( Machado et al 2018 ), major mountain ranges act as significant obstacles to migration for European barn owls and can generate genetic structure.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies showed that barn owls survived the last glaciation by taking refuge in the Iberian Peninsula and maybe even in emerged land in the now immerged Bay of Biscay ( Antoniazza et al 2014 ; Machado et al 2021 ). The observed distribution of diversity in Europe, and especially the specific makeup of the Italian populations, is best explained by a demographic model with two glacial refugia—one in Iberia and a second in Italy, derived from the Iberian population before the glaciation ( fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations